(untitled) (Research, Society and Development, 2022)
Objective: To identify through the literature the effects of music therapy on children and adolescents eligible for palliative care. Methodology: Integrative review using full scientific articles indexed in PubMed, LILACS and CINAHL databases published in Portuguese, English and Spanish. The search took place from April to June 2022, with the guiding question: What are the effects of music therapy in the care of children and adolescents eligible for palliative care? Results: Five articles were selected, two of which were performed in Brazil and the others in China, Iraq and the United States. Music therapy has been shown to be beneficial for relief and pain reduction, as well as for the improvement of the emotional state as sadness and negative feelings, being an accepted intervention for children and adolescents eligible for palliative care. Conclusion: This review made it possible to observe that music therapy is beneficial for the improvement of physiological data, as well as for the comfort of children and adolescents eligible for palliative care.